Analisis Pemahaman Fungsi Invers Pada Guru Matematika Berdasarkan Teori Skemp - Ida Rosita; Fauzia Hajar Hasanah; Dewi Wulansari (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2021)
This study aims to analyze the ability of understanding in the form of analytical and graphical representations of inverse functions based on Skemp Theory. The type of research is used a case study. Subjects consisted of one high school math teacher and one junior high school math teacher. Data collection techniques using description task and interview instruments. The description questions include a decontextual task to analyze the extent of understanding used by mathematics teachers doing inverse function task. The methodology and theoretical framework used aims to interpret mathematics teacher activities in analyzing task. The data analysis of the comprehension ability used by the math teacher was presented when answering the inverse decontextual task and making conclusions about their understanding based on their activities. The results showed that the subjects studied had the ability of relational understanding and instrumental understanding based on Skemp Theory.